Adalimumab mitigates ovarian ischemia–reperfusion injury in rats by regulating oxidative stress, apoptosis and resolution of inflammation. Issue 2 (24th October 2018) - Beyazit, Fatma; Büyük, Başak; Turkon, Hakan; Elmas, Sait; Uzun, Metehan
Abstract: Aim: Ovarian torsion is a rare but an important reason of acute lower abdominal pain in women and associated with serious morbidity and mortality, if not treated promptly. The aim of this study was to evaluate the effects of an antitumor necrosis factor‐α antibody on ovarian torsion in a rat model of ischemia–reperfusion (I/R) injury. Methods: Forty female Wistar Albino rats were used in the present study. The rats were randomly divided into four groups: group I (sham), group II (I/R), group III (I/R + isotonic saline) and group IV (I/R + adalimumab). The I/R model was induced by torsion of both ovaries. Immunohistochemical staining for interleukin‐1β (IL‐1β), nuclear factor‐κB (NF‐κB), and inducible nitric oxide synthase was performed. Tissue and serum oxidative stress markers in conjunction with apoptotic index (AI) with the terminal deoxynucleotidyl transferase dUTP nick end labeling method were also calculated. Results: Tissue total oxidant status, oxidative stress index and nitric oxide values were significantly decreased, and tissue total antioxidant status was found to be increased in group IV. Inflammation, vascular congestion and hemorrhagia were significantly lower in adalimumab‐treated group. Serum oxidative stress markers and tissue malondialdehyde levels did not differ in study groups. The AI was significantly increased in groups 2 and 3. Adalimumab treatment significantly decreased the AI. Conclusion: Adalimumab therapy in rats attenuated I/R induced ovarian injury, possibly suppressing inflammation, inhibiting oxidative stress, and altering apoptotic pathways.